2001
DOI: 10.1592/phco.21.12.175s.34506
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Perspective for the Management of Invasive Fungal Infections: Focus on IDSA Guidelines

Abstract: Invasive fungal infections, especially candidiasis and aspergillosis, are a major cause of morbidity and mortality. Many controversies surround the management of these infections. A critical overview of the recent Infectious Diseases Society of America practice guidelines is provided, as are comments on both the conundrums and future perspectives in medical mycology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 126 publications
0
16
0
Order By: Relevance
“…However, clinical relevance might best be related to patient factors (e.g., recovery of neutropenia, cessation of glucocorticoid therapy) and not intrinsically related to the susceptibility of the fungus itself. No clinical study to date has answered convincingly whether combination therapy is more beneficial than therapy with amphotericin B alone [50]. In fact, only 1 prospective trial of combination therapy to treat patients has been reported [10], whereas only 1 other has been done (unpublished data).…”
Section: /Mic A] + [(Mic B In Combination)/mic B]mentioning
confidence: 99%
“…However, clinical relevance might best be related to patient factors (e.g., recovery of neutropenia, cessation of glucocorticoid therapy) and not intrinsically related to the susceptibility of the fungus itself. No clinical study to date has answered convincingly whether combination therapy is more beneficial than therapy with amphotericin B alone [50]. In fact, only 1 prospective trial of combination therapy to treat patients has been reported [10], whereas only 1 other has been done (unpublished data).…”
Section: /Mic A] + [(Mic B In Combination)/mic B]mentioning
confidence: 99%
“…Therefore, the echinocandin in vitro activity end point is morphological change, not clearing of the medium. Echinocandins are generally fungicidal in vitro, although not as rapidly as amphotericin B [14,18], but appear to be more fungistatic against Aspergillus [19]. As a class, these agents are not metabolized through the cytochrome P-450 enzyme system but through a presumed O-methyltransferase, lessening some of the drug interactions and side effects seen with the azole class.…”
Section: Overview Of Antifungal Classesmentioning
confidence: 99%
“…The recommended dosage of amphotericin B for IA is 1.0-1.5 mg/kg/day, and optimal duration of therapy is unknown but largely dependent on underlying disease, extent of the patient's IA, resolution of neutropenia, lessening immunosuppression,and the return of graft function following bone marrow or organ transplantation [7,19]. There is no total dose of amphotericin B recommended, and the suggested key to success is to give a high dose in the first 2 weeks of therapy and to change to another treatment if amphotericin B therapy fails [3].…”
Section: Polyenesmentioning
confidence: 99%
“…Therefore, impressions and marketing may be instrumental in creating perceived gold standards. Finding consensus on what is standard treatment of mycoses has been challenging [28] and this is recognized even in recent guidelines [29,30]. Key problems are the heterogeneity of the host; difficulties in early diagnosis; and defining the effects of prior, concomitant, or subsequent antifungal therapies; and the fact that multiple additional interventions are often performed at the same time.…”
Section: Discussionmentioning
confidence: 99%